Research of key approaches to responsive website development and their practical application - Filippova, Lyubov; Svidelskyi, Rostislav (Technology audit and production reserves, 2016)
The perspectives of responsive approach in web development in the design and layout implementation by web developers are analyzed. It is due to, primarily, a significant increase in mobile internet traffic and increase the diversity of electronic devices. The optimal responsive approach compared with the development of certain versions of websites for different devices is analyzed. It is shown that responsive approach provides greater website support by all devices. This is achieved thanks to its particular advantages, including the use of HTML and CSS code to display a website on all devices and adapting the content to the width of the browser. Definition of the term «responsive web design» by different authors and scholars are considered. The basic components using this approach are theoretically described and practical examples are given. In particular, the use of relative values for a given width of the container and child elements, use of media queries for laptops, tablets and mobile phones. «Mobile-first» approach is investigated as an independent web development philosophy and at the same time, as an integral part of responsive website page layout, its advantages and disadvantages. An example for the analysis of website responsibility was selected resource of the American newspaper «The Boston Globe». With a significant every year growth of screen resolution the issue of JPEG format feasibility for displaying graphics of the website is became actual. Therefore, the analysis of SVG format is carried out. Graphics clarity isn’t lost for it and the output file size much smaller as a result. It is shown that this is achieved through describing two-dimensional graphics in XML and using three types of objects: shapes, images and text. Despite the fact that today there is access to many popular frameworks that are already implemented responsibility, many companies continue to develop multiple versions of websites for different devices. This significantly increases the resource costs for their support, and as a result they are available for a small portion of users.